EFFECT OF AEGLE MARMELOS AND MURRAYA KOENIGII ON ESTRUS INDUCTION, CONCEPTION AND CALVING RATE IN DELAYED PUBERTAL HEIFERS UNDER FIELD CONDITION - KUMAWAT, BL; DAS, GK; NARAYANAN, K; MEHROTRA, S; PRASAD, JK; GHOSH, SK; KUMAR, H (The Indian Journal of Animal Reproduction, 2016)
Fertility response in delayed pubertal heifers (n=13) treated for 9 days with herbal blend of Aegle marmelos and Murraya koenigii leaf powder was evaluated in terms of estrus response, conception and calving rates in comparison to untreated controls (n=13). Following initiation of treatment, behavioral estrus was exhibited in 92.3% (12/13) heifers after 11.25±1.91 days. The conception and calving rates (p<0.05) in treated heifers were 61.5% and 53.8%, respectively, in comparison to 23.1% and 7.7% in their respective control counterparts. The current study revealed the pro-fertility potential of medicinal plants to induce fertile estrus in delayed pubertal heifers.